Evaluation of urinary NGAL level in children with congenital heart disease as a possible early indicator of nephropathy - Hossein Emad Momtaz; Asadolah Tanasan; Majid Godini (Society of Diabetic Nephropathy Prevention, 2021)
Introduction: Nephropathy as a consequence of congenital heart disease (CHD), especially cyanotic heart disease, has been detected since past decades. However, lack of a diagnostic method at early stages of the disease, caused patients referring when nephropathy is established and also complicated with severe proteinuria and renal failure. Urinary neutrophil gelatinase-associated lipocalin (NGAL) is known as one of the newest biomarkers for early detection of renal parenchymal damage. In this study, we attempted to evaluate the role of urinary NGAL level in early detection of nephropathy in pediatrics with CHD. Objectives: The aim of this study was to evaluate urinary NGAL as a potential biomarker for the early detection of renal involvement in children with CHD. Patients and Methods: In this case-control study, urinary NGAL levels of 42 children with CHD (case group) and 42 healthy children (control group) with the matched ages were measured. Afterward, we compared mean urinary NGAL levels between these two groups to find a possible significant difference. Results: In this study, mean urinary NGAL level in patients with CHD and healthy children was 3.83 μg/mL and 1.87 μg/mL, respectively. Although the mean urine NGAL level was higher in children with CHD compared to healthy children, this difference was not statistically significant. Conclusion: in this study, it can be concluded that, urinary NGAL level cannot be used as an early diagnostic test of nephropathy in children with CHD.